Systems thinking for water security. Issue 3 (3rd July 2022) - Polaine, Xanthe K.; Dawson, Richard; Walsh, Claire L.; Amezaga, Jaime; Peña-Varón, Miguel; Lee, Cindy; Rao, Sandhya
ABSTRACT: Water security covers a wide range of issues and risks to people, the natural and built environment, the economy, and interactions between these. This breadth creates an interconnected complexity and the potential for perceived intractability. Tackling water security meaningfully therefore requires a judgement in balancing the holistic nature of water security with reductionist understanding of key processes and elements. This paper demonstrates that systems thinking can be adapted to achieve this through different systems framings of water security, tailored to local context. Through four case studies, we show how systems thinking has been adapted and applied to fit the contextual analysis and management of multiple water security issues. We show how this approach has dissolved disciplinary and sectoral silos; changed the spatial scale at which water security is addressed; improved data acquisition and analysis to better understand relationships between sub-systems; and integrated socio-ecological issues of justice and power with more traditional bio-physical understandings of water security. This is an important step towards turning systems thinking into systems transformation and making the concept of water security actionable and accessible to policy, planning, and practice.